1957
DOI: 10.1111/j.1365-2621.1957.tb17521.x
|View full text |Cite
|
Sign up to set email alerts
|

A NEW TREATMENT OF HYGROSCOPIC EQUILIBRIA: APPLICATION TO WALNUTS (JUGLANS REGIA) AND OTHER FOODSa

Abstract: Hygroscopic equilibrium data have been obtained for a wide variety of materials, because the derived moisture sorption isotherms serve a number of useful functions. They may be employed : to define limits for the dehydration of fruits, vegetables, nuts, etc. (28); to estimate moisture content changes under any given condition of temperature and humidity (28); to evaluate processing variables and to distinguish differences between grades or varieties of agricultural commodities (23,27); to aid in the selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

1959
1959
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 32 publications
1
14
0
2
Order By: Relevance
“…Através das isotermas pode-se determinar a monocamada, a qual além de estar relacionada com o início de uma série de reações químicas de deterioração dos alimentos, representa o ponto de maior gasto de energia em um processo de secagem [11,13,20,22].…”
Section: Discussionunclassified
“…Através das isotermas pode-se determinar a monocamada, a qual além de estar relacionada com o início de uma série de reações químicas de deterioração dos alimentos, representa o ponto de maior gasto de energia em um processo de secagem [11,13,20,22].…”
Section: Discussionunclassified
“…Using a modified Henderson (1952) equation Rockland (1957) observed that experimental points of sorption data generally described three intersecting straight lines which he called localised isotherms (LIs) and which were assumed to represent the coverage of three types of bound water namely; the monolayer, multilayer and free water (Rockland, 1969). From the present studies the BET multilayer (Brunauer et al.…”
Section: Discussionmentioning
confidence: 99%
“…The equilibrium moisture is found from the empirical equation for English walnuts given by Rockland (1957):…”
Section: Wimentioning
confidence: 99%